Practical application of Cari Screen test and ecological balance hypothesis - Mikołajczyk, Joanna; Rojek, Rafał; Gońda-Domin, Magdalena; Wieczkowska, Ilona; Węsierska, Karolina (Journal of Stomatology, 2017)
Aim or Purpose: The aim of study is to determine status of oral health and assess efficacy of Cari Screen test to estimate risk of caries in 3 year-old children. The ecological balance hypothesis suggests that risk of caries increases cellular activity of dental plaque bacteria. Materials-Methods: The study was conducted in a group of 30 randomly selected 3-year-old children. Researcher determined number of dmft and the presence of tooth decay and presence of dental plaque. Survey of oral cavity has been completed by Cari Screen test. Interpretation of results was based on simple scale: 0-1500 - low activity of bacteria, above 1500 - high activity of bacteria. Results: Occurrence of caries reached 60% in the 3-year-olds, and the average number of dmft was found to be 3,3. During the Cari Screen test study, problems of compliance with manufacturer's recommendations related to difficulty of cooperation of such young patients. Preliminary analysis of the results of CS indicates a higher activity of bacteria in children with active caries, however to formulate clear conclusions further research is required. Conclusions: The level of dental caries among examined children is alarmingly high. Cari Screen test used to examine 3-year-old children turned out difficult to perform. This led to such of modification of the procedure, which allowed correct use of this tool among youngest patients. New tools, which fit into more recent hypothesis development of dental caries, allow us to study the activity of pathogens and more accurately estimate the risk of this disease.